Chapter 20 The Council of Europe’s Approach towards Ageism (2018)
This chapter analyses treaties adopted by states at the Council of Europe forum, as well as its soft law, in order to answer the following questions: how is ageism understood by this forum; what measures have been proposed to eliminate ageism; and are the soft law documents helpful for a pro-old-age interpretation of existing human rights treaties? Arguments are provided to suggest that the existing human rights monitoring bodies of the Council of Europe might have an important role to play in the elimination of ageism in Europe. The role of European Court of Human Rights jurisprudence and the Council of Europe’s soft law are examined, and the argument is made that this organization has a massive potential to positively affect the laws and policies of its members states in the area of protecting the rights of older adults, but that this is contingent on member states’ awareness and political will.